Blood Pressure, Hypertension, and the Risk of Aortic Dissection Incidence and Mortality: Results From the J-SCH Study, the UK Biobank Study, and a Meta-Analysis of Cohort Studies. Issue 9 (1st March 2022) - Hibino, Makoto; Otaki, Yoichiro; Kobeissi, Elsa; Pan, Han; Hibino, Hiromi; Taddese, Henock; Majeed, Azeem; Verma, Subodh; Konta, Tsuneo; Yamagata, Kunihiro; Fujimoto, Shouichi; Tsuruya, Kazuhiko; et al.
Abstract : Background: Hypertension or elevated blood pressure (BP) is an important risk factor for aortic dissection (AD); however, few prospective studies on this topic have been published. We investigated the association between hypertension/elevated BP and AD in 2 cohorts and conducted a meta-analysis of published prospective studies, including these 2 studies. Methods: We analyzed data from the J-SHC study (Japan-Specific Health Checkups) and UK Biobank, which prospectively followed up 534 378 and 502 424 participants, respectively. Multivariable Cox regression was used to estimate hazard ratios and 95% CIs for the association of hypertension/elevated BP with AD incidence in the UK Biobank and AD mortality in the J-SHC Study. In the meta-analysis, summary relative risks were calculated with random-effects models. A potential nonlinear dose-response relationship between BP and AD was tested with fractional polynomial models, and the best-fitting second-order fractional polynomial regression model was determined. Results: In the J-SHC study and UK Biobank, there were 84 and 182 ADs during the 4- and 9-year follow-up, and the adjusted hazard ratios of AD were 3.57 (95% CI, 2.17–6.11) and 2.68 (95% CI, 1.78–4.04) in hypertensive individuals, 1.33 (95% CI, 1.05–1.68) and 1.27 (95% CI, 1.11–1.48) per 20–mm Hg increase in systolic BP (SBP), and 1.67 (95% CI, 1.40–2.00) and 1.66 (95% CI, 1.46–1.89) per 10-mm Hg increase in diastolic BP (DBP), respectively. In the meta-analysis, the summary relative risks were 3.07 (95% CI, 2.15–4.38, I 2 =76.7%, n=7 studies, 2818 ADs, 4 563 501 participants) for hypertension and 1.39 (95% CI, 1.16–1.66, I 2 =47.7%, n=3) and 1.79 (95% CI: 1.51–2.12, I 2 = 57.0%, n=3) per 20–mm Hg increase in SBP and per 10–mm Hg increase in DBP, respectively. The AD risk showed a strong, positive dose-response relationship with SBP and even more so with DBP. The risk of AD in the nonlinear dose-response analysis was significant at SBP >132 mm Hg and DBP >75 mm Hg. Conclusions: Hypertension and elevated SBP and DBP are associated with a high risk of AD. The risk of AD was positively dose dependent, even within the normal BP range. These findings provide further evidence for the optimization of BP to prevent AD.